Benchmark shielding calculations for fusion and accelerator-driven sub-critical systems - Iwamoto, Yosuke; Tsuda, Shuichi; Ogawa, Tatsuhiko (Frontiers in Energy Research, 2023)
We conducted benchmark calculations of neutron-shielding experiments for fusion applications such as (1) Neutron spectra in iron shields with 14 MeV neutrons; and (2) Leakage neutron spectra from various sphere piles by 14 MeV neutrons, and for Accelerator-Driven Sub-Critical system (ADS) such as (3) Neutron energy spectra after transmission through iron and concrete shields using a quasi-monochromatic neutron source, (4) Thick target neutron yield produced by high-energy heavy ion incidence on a thick target, and (5) Induced radio activity in concrete exposed to secondary particles produced by heavy-ion incident reaction on an iron target by using the Particle and Heavy Ion Transport code System (PHITS). For case (1), the calculated neutron energy spectra using the nuclear data libraries, JENDL-4.0, agreed with the experimental data in iron shields. For the cases (2) of Al, Ti, Cr, and As piles, the neutron energy spectra calculated with JENDL-4.0 agreed with the experimental results well. For the case (3), the neutron spectra calculated with JENDL-4.0/HE reproduced the experimental data because the proton data library of 7Li can produce source neutrons for proton incident reactions. For the case (4), calculated results for thick target neutron spectra produced by a 400 MeV per nucleon carbon incident reaction on lead reproduced the experimental data well. For the case (5) with a neutron source produced by the 200–400 MeV per nucleon heavy-ion incident reaction, the calculated results of the reaction rate depth profiles of 197Au (n, γ)198Au reactions reproduced the experimental results within a factor of 2. Overall, PHITS with nuclear data libraries reproduced the experimental data sufficiently well. Thus, PHITS has a potential application in the design of advanced reactor systems, such as fusion and ADS facilities. This experimental data are also useful in validating nuclear reaction models in other Monte Carlo codes and evaluating nuclear data libraries for advanced reactor systems.